Masalah Transportasi menggunakan Kombinasi Distribusi Normal dengan Root Mean Square (RMS) untuk Solusi Layak Awal dan Sirisha-Viola Method (SVM) untuk Solusi Optimal - Saadah, Miftahus; Affandi, Pardi (Equiva Journal, 2025)
The objective of this research is to find the best logistics solution for various purposes at minimal cost. The development of a new initial feasible solution (IBFS) algorithm is the first step toward finding the optimal solution. This new method for initial feasible solutions reduces the number of iterations and produces the best solution for transportation problems at an early stage. The literature review covers various IBFS methods. The new IBFS was discovered using statistical techniques such as normal distribution and root mean square techniques. A transportation problem is converted into a normal distribution, and the penalty is determined using the root mean square method. The normal distribution value can be calculated using Excel Solver. In the second step, a step-by-step method is used to find the optimal solution. Numerical calculations are used to calculate the research results and compared with the Sirisha-Viola method in determining a feasible optimal solution.